Medical Analysis Based on Agri And Human Healthcare Under Mining Techniques - Pavithra, A; Snehalatha, V (International Journal of Computer Sciences and Engineering, 2025)
Right from the Stone Age one law is governing the market for every generation Furthermore that well acknowledged law is “Law of Demand & Supply”. ICT is not far away from this law. It is a well-known fact that when cyber world is marching quickly towards higher form of innovative evolution, Cloud Processing has entered as backbone support to ICT as a tool for better cost performance. It is a platform, which is highly governed by the law of “Demand &Supply”, whether it is Banking, Healthcare or Agriculture, all are in need of this innovation to make their execution as cost powerful as conceivable Furthermore, ubiquitous in functionality. As by the law, Demand Furthermore, Supply both go hand-to-hand. This paper presents some of the demand facets Furthermore, corresponding supply administrations for banking, farming Furthermore, healthcare. It enables programming architect to make the system of any division to build up fully fledged working area in due consideration of cloud computing. Keyword: Banking Furthermore, Financial System (BFS), Cloud Computing, Hospital Administration Information System (HMIS), Information Correspondence Innovation (ICT), SaaS Application, Total Cost of Possession (TCO).